Interpretasi Ajaran Panca Sradha dalam Lontar Tutur Kumara Tattwa - I Putu Febriyasa Suryanan; I Made Arsa Wiguna; Ni Nyoman Mariani (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
This research has a purpose to reveal the essence of Hindu religious teaching in Lontar Tutur Kumara Tattwa, using by literarture study method and interview techniques, it is hoped this research can reveal the teaching of Panca Sradha (five beliefs of Hindu), namely belief in God through manisfestation of God who is an Imanen (Saguna Brahman) with a form of Bhatara Guru as teacher of the Gods, there is a parable of Bhatara as sun and humans are like jar from the parable is described that there are sprinkling of paramatman from within humans, the self control doing by human to create a good karmaphala so as to achieve moksa and avoid rebirth (punarbhwa).